Complex Job Design and Layers of Hierarchy - Giovanni Russo; Gijs Van Houten (Institute of Labor Economics (IZA), 2021)
The main function of hierarchies is to coordinate activities within an organisation, but a hierarchical structure also provides work incentives, by offering the prospect of hierarchical mobility. An alternative way for organisations to motivate workers is through job design. In organisations offering rewarding jobs, the incentivising role of hierarchies may become obsolete, and the number of hierarchical levels can be reduced. Two job design features are particularly relevant: autonomy and problem solving. We investigate the relationship between the number of hierarchical layers and job design features empirically using the European Company Survey (ECS 2019). We find that the extent of the adoption of both complex job design and autonomous teamwork are negatively associated with the number of hierarchical layers. However, the association between complex job design and the number of hierarchical layers is weakened, and in some cases disappears, in larger organisations where hierarchies have a more important coordination role and it is weakened when the knowledge acquisition costs are high. The use of autonomous teams is robustly negatively associated with the number of hierarchical layers.
Keywords: M51; L20; M50; 330; job design; hierarchies; job complexity